Skeletal Muscle Mitochondrial Impairment in Cirrhosis-Induced Sarcopenia - Omid Farshad; Mohammad Mehdi Ommati; Jale Yüzügülen; Sahand Alizadeh; Khadijeh Mousavi; Negar Azarpira; Anahita Marhonian; Akram Jamshidzadeh; Reza Heidari (Shiraz University of Medical Sciences, 2020)
Cirrhosis-associated muscle mass loss or sarcopenia is a common complication (17-30% prevalence) in cirrhotic patients. However, the pathogenesis of this complication is poorly understood. Therefore, finding the mechanisms of sarcopenia could lead to the development of therapeutic strategies against this complication. In the current study, rats underwent bile duct ligation (BDL) surgery, and their skeletal muscle (gastrocnemius; GS) was isolated and assessed 28 and 56 days after BDL operation. Significant increase in biomarkers of oxidative stress, including reactive oxygen species (ROS) formation, lipid peroxidation, and increased oxidized glutathione (GSSG) levels were detected in the muscle of cirrhotic animals. Skeletal muscle tissue antioxidant capacity and reduced glutathione (GSH) were also significantly decreased in BDL rats. Moreover, deterioration of several mitochondrial indices, including mitochondrial depolarization, increased mitochondrial permeabilization, depleted ATP reservoirs, and decreased mitochondrial dehydrogenases activity, were evident in the GS isolated from cirrhotic rats. Based on these data, oxidative stress and mitochondrial impairment seem to play as primary mechanisms of cirrhosis-induced sarcopenia.